IFPRI Kenya launches the IDEA series to foster knowledge exchange - Ayalew, Hailemariam; Kimaiyo, Faith Chepkemoi; Karachiwalla, Naureen (CGIAR, 2024)
On November 18, 2024, the IFPRI Kenya office proudly launched the first session of the IFPRI Development Economics Africa Seminar (IDEAS) Series at the ILRI Nairobi Campus. This is part of seminar series under the CGIAR Initiatives on National Polices and Strategies (NPS).